2016
DOI: 10.15713/ins.jcri.140
|View full text |Cite
|
Sign up to set email alerts
|

A molecular insight in the prevalence of odontogenic tumor

Abstract: Odontogenic tumors (OT) encompass a diverse collection of lesions that ranges from hamartomas to benign and malignant neoplastic lesions of erratic aggressiveness. The progress and development of OT are influenced by variation of many kinds of genes and molecules. Genetic instability is a hallmark of cancer. This review illustrate a concurrent sketch of the recent updating of the molecular and genetic alterations linked with the growth and development of OT, including oncogenes, tumor-suppressor genes, oncovir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It can potentially cause bone destruction, with well-defined multilocular radiolucencies encircled by Prevalence and Epidemiological Profile of Ameloblastoma in India: A Systematic Review and Meta-Analyses cortical bone sclerosis, notably in solid ameloblastoma. It is worthy to note that the vast majority of ameloblastoma studies conducted in India revealed a substantial male predisposition (Anila et al, 2021;Bhattacharjee et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It can potentially cause bone destruction, with well-defined multilocular radiolucencies encircled by Prevalence and Epidemiological Profile of Ameloblastoma in India: A Systematic Review and Meta-Analyses cortical bone sclerosis, notably in solid ameloblastoma. It is worthy to note that the vast majority of ameloblastoma studies conducted in India revealed a substantial male predisposition (Anila et al, 2021;Bhattacharjee et al, 2016).…”
Section: Introductionmentioning
confidence: 99%